Farmers Perception of Sources of Information in Relation to Adoption of Improved Rice Technology by Farmers in the Inland Valley Swamps of Middle-Belt zone of Nigeria - E B Tologbonse; O Mesini; J H Tsado (Journal of Agricultural Extension, 2006)
The objective of this study was to determine the fanners perception of information sources and adoption of rice technology and its relationship with farmers socioeconomic characteristics in the inland Valley Swamps (IVS). Using survey research, a pre-tested structured interview scheduled was used to collect information from 500 rice farmers that were randomly selected from four States including the Federal Capital Territory, Abuja from the Middle-Belt zone of Nigeria. Descriptive and inferential statistics were used to analyze the data. About 96% of the respondents adopted fertilizer application and only 29.8% adopted iron toxicity control. The results of the PPMC analysis revealed a significant positive correlation between adoption and household size involved in farming (r =0.095; p < 0.05), and extension contact (r =0.31;p < 0.05). The result of the Chi-square analysis revealed a significant relationship between adoption and religion(X2 = 9.94;p < 0.05), ethnic group (X2 =8.57;p < 05 ), awareness of technology ( r = 0.392, p < 0.05) and information source (X2 = 59.49; p < 0.01). This study revealed that extension publication, television and newspaper are considered as not important sources of agricultural information while extension agents, demonstration/SPAT, neighbour/friends, radio, field-day andparents are important sources of agricultural information. The study also revealed that the sources ofinformation awareness variesfrom technology to technology. It is recommended that, the extension agents be encouraged and effort be made to emphasize andpopularize the use of mediated information sources and extension research methodology in order to increase the extension coverage area which is likely to increase adoption.